Travestis e prisões : a experiência social e a materialidade do sexo e do gênero sob o lusco-fusco do cárcere - Ferreira, Guilherme Gomes (2014)
The presente text discusses about the social experiences of the travestis in prison, having as background the Central Prison of Porto Alegre. This analysis used the fundamentals of the dialectical materialism and feminist grounds (especially the intersectional one), queer theory and critical criminology, toward a marxist queer perspective. Studying the social experiences of the travesti population in prison implies to recognize the presence of denied rights and non-responded needs, since it is known that the gender identities, which are different from the ones recognized as consistent with a sex/gender binary system, are historically repressed and scrutinized by the ideological apparatuses of the Estate, especially the ones attached to the criminal justice system. It was used, ass a qualitative nature methodology, the bibliographic and document research used to accomplish the theoretical study of the theme, the non-structured interviews through oral history technique applied to subjects and participant observation using a field diary. The interviews were performed with a focal group of twelve prisoner travestis and two male partners of theirs; individual interviews with one prisoner homosexual man, three travestis who have experienced prison and four prison employees, totalizing 22 investigation subjects. The oral history appears as technique in the non-structured interviews and focal group through a script of guided topics. As for the participant observation, the script developed embodied the field diary. The interpretation of the data was attained by discursive textual analysis. It was possible to consider that the arrest of the travestis give the prison distinct patterns of control over bodies, not experienced so far, which the prison experience become an instrument for deepening of the violence suffered in daily life. It occurs due to the criminal justice selective system consider as social markers race/ethnicity and social class, or in other words, determinations that put them previously socially vulnerable. The creation of a specific room, thus, is a way of confronting collectively organized by the travestis according to their interests for more institutional protection. On the other hand, this same kind of protection also oppresses the travestis in the most perverse ways, such as the non-access to education and work inside the prison system; their relationships with other prisoners and the institutional transphobia; the determined behavior patterns; the poor access to health; the family abandonment; the criminal control.